2002
DOI: 10.1161/01.res.0000015214.40360.84
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mitochondrial Inhibition on Global and Local [Ca 2+ ] i in Rat Tail Artery

Abstract: Abstract-Inhibition of oxidative metabolism is often found to decrease contractility of systemic vascular smooth muscle, but not to reduce global [Ca 2ϩ ] i . In the present study, we probe the hypothesis that it is associated with an altered pattern of intracellular Ca 2ϩ oscillations (waves) influencing force development. In the rat tail artery, mitochondrial inhibitors (rotenone, antimycin A, and cyanide) reduced ␣ 1 -adrenoceptor-stimulated force by 50% to 80%, but did not reduce global [Ca 2ϩ ] i . Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…In isolated mitochondria, antimycin A stimulates superoxide production (43,48), but, as with other electron transport chain inhibitors, this may not occur in intact tissues (32,39). In the present study, antimycin A impaired contraction to PGF 2␣ , which is concordant with effects in other models (50,63). Antimycin A alters Ca 2ϩ handling (50) and decreases ATP levels (3,8,68), each of which could explain the reduction of contraction to PGF 2␣ observed in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…In isolated mitochondria, antimycin A stimulates superoxide production (43,48), but, as with other electron transport chain inhibitors, this may not occur in intact tissues (32,39). In the present study, antimycin A impaired contraction to PGF 2␣ , which is concordant with effects in other models (50,63). Antimycin A alters Ca 2ϩ handling (50) and decreases ATP levels (3,8,68), each of which could explain the reduction of contraction to PGF 2␣ observed in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Mitochondria were shown to modulate control IP 3 -evoked Ca 2+ release by operating within an IP 3 R cluster, and when mitochondrial Ca 2+ uptake was prevented, a localised Ca 2+ release from an IP 3 R (a Ca 2+ puff) was inhibited (Fig. 3) [17,22,57,76,78]. The results were consistent with Ca 2+ uptake by mitochondria limiting a negative feedback effect of Ca 2+ on the IP 3 R cluster.…”
Section: Mitochondrial Regulation Of Smooth Muscle Ca 2+ Signalssupporting
confidence: 69%
“…Several early studies have shown that Ca 2+ increases evoked by IP 3 -generating agonists were almost fully inhibited when mitochondrial Ca 2+ uptake was prevented [17,22,57,76,78], i.e. mitochondria appeared to determine whether or not a Ca 2+ signal occurred at all.…”
Section: Mitochondrial Regulation Of Smooth Muscle Ca 2+ Signalsmentioning
confidence: 99%
“…Our data have shown that the presence of FCCP not only caused important alterations in CChinduced Ca 2+ increase but also changed ΔΨm substantially. In fact, the influence of mitochondria on Ca 2+ signaling and contraction in vascular smooth muscles was well studied and some workers have found that the stimuli that evoke cytosolic Ca 2+ rise also induced mitochondrial Ca 2+ uptake (Drummond and Tuft, 1999;Montell et al, 2002;Swärd et al, 2002;Szado et al, 2003). In other types of muscles, cytosolic Ca 2+ rise and transient Ca 2+ uptake into mitochondria were followed by a rapid decrease in Ca 2+ levels inside these organelles (McCarron and Muir, 1999;Szalai et al, 2000;Robert et al, 2001;Rudolf et al, 2004).…”
Section: Anti-desmin Dapi Mergedmentioning
confidence: 99%